2022
DOI: 10.18408/ahuri7127201
|View full text |Cite
|
Sign up to set email alerts
|

Assisting first home buyers: an international policy review

Abstract: Related reports and documentsInquiry into financing first home ownership: opportunities and challenges https://www.ahuri.edu.au/research-in-progress/Inquiry-intofinancing-first-home-ownership-opportunities-and-challenges AHURI AHURI is a national independent research network with an expert not-for-profit research management company, AHURI Limited, at its centre. AHURI's mission is to deliver high quality research that influences policy development and practice change to improve the housing and urban environmen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(53 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…This study was conducted during the COVID-19 pandemic in Australia and challenges associated housing affordability and availability may have been exacerbated disproportionally by the lack of housing available in rural communities during this time due to unprecedented purchase and movement of people to rural regional communities. 41 Similarly, recruitment was enhanced and hindered in different communities during this time. Another possible limitation, despite the robust development of the tool, 11 may be that the factors were limited to 50 and other factors may exist that also impact pharmacist workforce.…”
Section: Limitationsmentioning
confidence: 91%
“…This study was conducted during the COVID-19 pandemic in Australia and challenges associated housing affordability and availability may have been exacerbated disproportionally by the lack of housing available in rural communities during this time due to unprecedented purchase and movement of people to rural regional communities. 41 Similarly, recruitment was enhanced and hindered in different communities during this time. Another possible limitation, despite the robust development of the tool, 11 may be that the factors were limited to 50 and other factors may exist that also impact pharmacist workforce.…”
Section: Limitationsmentioning
confidence: 91%
“…In supporting home owners specifically, home purchase subsidies had existed in various forms since 1964, and were finally eliminated in 1990 (Bourassa, Greig et al 1995). Critics of these schemes suggested that the impact of these grants were to bring forward first home owner purchase for those who would have purchased anyway (Paris, Beer et al 1993;Pawson, Martin et al 2022), thus having little impact on long term trajectory and rates of home ownership.…”
Section: First Home Buyer Schemes and Housing Financingmentioning
confidence: 99%
“…There are a variety of models that place differing emphasis on rights and responsibilities of those involved, divisions of value and who the subsidy is targeted towards (Pinnegar, Easthope et al 2009). Today, there are limited affordable housing finance schemes with two continuing examples including Keystart and HomeStart Finance in Western Australia and South Australia respectively, provided by government backed, arms-length, agencies (Pawson, Martin et al 2022;Pawson, Milligan et al 2020).…”
Section: Supported Ownership and Shared Equity Modelsmentioning
confidence: 99%
See 2 more Smart Citations